Immunomodulatory activity of Buchholzia coriacea seed methanol extract on Trypanosoma brucei brucei infected mice - James I. Eze; Chioma F. Ekelozie; Nwakego E. Nweze (Taylor & Francis Group, 2017)
Context: The seeds of Buchholzia coriacea Engler (Capparaceae) are used in Eastern Nigeria to treat feverish conditions, and to treat malaria and sleeping sickness that cause fever. Objective: The current study assesses the immunomodulatory activity of Buchholzia coriacea seed extract on Trypanosoma brucei brucei infected mice. Materials and methods: Delayed hypersensitivity reaction, humoral antibody response and in-vivo leucocyte mobilization tests were assessed in three different experiments to determine the effect of the extract on immune response. Seventy-five (75) mice (25 mice per experiment) were used for the study and were each infected with 1.00 × 106 trypanosomes intra-peritoneally. Groups A, B and C were given 250, 500 and 1000 mg/kg of the extract, respectively, group D received 7.5 mg/kg body weight of levamisole and group E was the control. Sheep RBCs were used as antigen. Results: The acute toxicity tests did not cause clinical signs or death within 24 h post treatment at all the doses tested. The extract inhibited delayed hypersensitivity reaction by 20.9 and 20.8% at 250 and 500 mg/kg, respectively, while at 1000 mg/kg, the paw size increased (−101.9%) when compared with the control. The extract elevated the antibody titre from 1.60 ± 0.40 for control to 8.00 ± 3.58 for 500 mg/kg group. The extract increased in total leucocytes counts. Discussion and conclusion: The extract has a very wide safety margin and was able to improve immune response. The results of the present study showed that Buchholzia coriacea seed methanol extract possesses immunostimulatory activity on trypanosome-infected mice.